HPV-Related Skin Phenotypes in Patients with Inborn Errors of Immunity - Assiya El Kettani; Fatima Ailal; Jalila El Bakkouri; Khalid Zerouali; Vivien Béziat; Emmanuelle Jouanguy; Jean-Laurent Casanova; Ahmed Aziz Bousfiha (Pathogens, 2022)
Patients with inborn errors of immunity (IEI) are prone to develop infections, either due to a broad spectrum of pathogens or to only one microbe. Since skin is a major barrier tissue, cutaneous infections are among the most prevalent in patients with IEI due to high exposures to many microbes. In the general population, human papillomaviruses (HPVs) cause asymptomatic or self-healing infections, but, in patients with IEI, unusual clinical expression of HPV infection is observed ranging from epidermodysplasia verruciformis (EV) (a rare disease due to β-HPVs) to profuse, persistent, and recalcitrant warts (due to α-, γ-, and μ-HPVs) or even tree man syndrome (due to HPV2). Mutations in EVER1, EVER2, and CIB1 are associated with EV phenotype; GATA2, CXCR4, and DOCK8 mutations are typically associated with extensive HPV infections, but there are several other IEI that are less frequently associated with severe HPV lesions. In this review, we describe clinical, immunological, and genetic patterns of IEI related to severe HPV cutaneous infections and propose an algorithm for diagnosis of IEI with severe warts associated, or not, with lymphopenia.